2013
DOI: 10.1124/dmd.113.051862
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of a Sarpogrelate Active Metabolite Is Mediated by UDP-Glucuronosyltransferases 1A4, 1A9, and 2B4

Abstract: Sarpogrelate is a selective serotonin 5-HT 2A -receptor antagonist used to treat patients with peripheral arterial disease. This drug is rapidly hydrolyzed to its main metabolite (R,, which is mainly excreted as a glucuronide conjugate. Sarpogrelate was also directly glucuronidated to an O-acyl glucuronide and a Nglucuronide by UDP-glucuronosyltransferases (UGTs) in human liver microsomes (HLMs). Since M-1 is pharmacologically more active than sarpogrelate, we examined glucuronidation of this metabolite in HLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Although plasma concentrations of M‐1 are <1/10 those of sarpogrelate, pharmacokinetic–pharmacodynamic modeling has shown that M‐1 is a more effective inhibitor of platelet aggregation than sarpogrelate . M‐1 further undergoes glucuronide conjugations to form inactive metabolites via UGT1A4, UGT1A9, and UGT2B4, which are mainly excreted into bile . It is necessary to develop analytical methods for the simultaneous quantification of sarpogrelate and M‐1 in biological fluids considering the efficacy of M‐1, polymorphisms of uridine diphosphate‐glucuronosyltransferases, or the drug–drug interactions related to uridine diphosphate‐glucuronosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Although plasma concentrations of M‐1 are <1/10 those of sarpogrelate, pharmacokinetic–pharmacodynamic modeling has shown that M‐1 is a more effective inhibitor of platelet aggregation than sarpogrelate . M‐1 further undergoes glucuronide conjugations to form inactive metabolites via UGT1A4, UGT1A9, and UGT2B4, which are mainly excreted into bile . It is necessary to develop analytical methods for the simultaneous quantification of sarpogrelate and M‐1 in biological fluids considering the efficacy of M‐1, polymorphisms of uridine diphosphate‐glucuronosyltransferases, or the drug–drug interactions related to uridine diphosphate‐glucuronosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…The active metabolite, M-1, reaches a C max of 49.3 ng/mL at 0.9 hour and exhibits slower elimination than sarpogrelate, with a half-life of 4.4 hours (Kim et al, 2013a). After absorption, sarpogrelate and M-1 further undergo glucuronide conjugations to form several metabolites, which are mainly excreted in bile (Kim et al, 2013b). Despite the wide use and excellent pharmacological properties of sarpogrelate, to date there is no information regarding the potential inhibitory effects of sarpogrelate and M-1 on human P450 isozymes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, INCA can be approximated as a racemate and its 5-/599-, 7-/799-, and 49-/4999-hydroxyl groups are different in spatial configuration to each other. Glucuronide metabolites of some racemates, such as flurbiprofen (Wang et al, 2011), propranolol (Yu et al, 2004(Yu et al, , 2010, propafenone (Xie and Zeng, 2010), and sarpogrelate metabolites (Kim et al, 2013), might be separated on a nonchiral stationary phase column. We believe that M2 also has two constitutional isomers even if they cannot be separated under the present HPLC conditions.…”
Section: Discussionmentioning
confidence: 99%